EMPLOYABILITY OF BS ACCOUNTANCY OF JOSE RIZAL MEMORIAL STATE UNIVERSITY (International Journal of Scientific Research and Management (IJSRM), 2022)
In a globalized, high-tech world with a competitive employment market, employability skills have grown in importance. Assessment of the graduates’ employability skills has come to need in order to strategically align curriculum with the industry’s demands. This study examined the employability of BS Accountancy graduates of Jose Rizal Memorial State University, Main Campus, Dapitan City. It used descriptive method of research utilizing questionnaire as the principal tool of gathering data. It revealed that most of the Accountancy graduates rated above average in all three skills: fundamental, personal management, and teamwork skills. Further, it was found out that there is no significant difference on the level of employability skills when analyzed according to sex, job position, industry/sector, length of service, and employment status. However, a significant difference was revealed on the personal management skills of BS Accountancy graduates when analyzed according to age. The Accountancy Department should keep abreast with the updates on related standards and provide hands-on training or extensive internship program to widen the skills development of the Accountancy students and adapt to technological advancement in the field of work. Future research is encouraged on this matter on the point of view of the employers in public, private, government, and academe sector.